Subjective Vitality Among 6th Year High School Students - Jasim, Dhiyaa Nimer; Al-Sabab, Azhar Mohammed Majeed (Al-Adab Journal, 2021)
In general, subjective vitality can be described as an individual feeling of the inner energy that drives the individual towards life with vigor and activity, which is affected by physiological and psychological factors, and since the sixth preparatory students are living a reality full of new changes day after day, they are subjected to psychological pressures that cast its shadow over Their academic reality, so the researcher chose that his study sample be students of the sixth intermediate school. The study aimed to identify the extent of their possession of subjective vitality in the educational process, and the statistically significant differences in their subjective vitality according to the variable of sex (male-female) and specialization (scientific-literary). The researcher built a scale of subjective vitality based on the theory of Ryan Frederick (Ryan, & Frederick, 1997), to fit with the objectives of the research and his sample, and the paragraphs of the Self-Vitality Scale were in its final form (40) paragraphs distributed into four domains. In two methods, the two groups' extremist method, and the relationship of the paragraph to the total degree, and to verify the objectives of the research, (468) students from the sixth middle school were selected from Baghdad governorate, and after applying the statement The results showed the following:1-The sixth preparatory students (males - females) have an intrinsic vitality.-2There are no statistically significant differences in the subjective vitality of the sixth preparatory students according to the variable of sex, specialization, and the interaction between sex and specialization.In light of the results of the research, the researcher puts forth a set of recommendations and proposals, some of which are for you Recommendations:The Ministry of Higher Education and Scientific Research should set plans with regard to lowering the high admission rates by expanding admissions, thus ensuring acceptance for students in the colleges they want in addition to not resorting to private colleges.